Influentials promote cooperation in spatial snowdrift games. (21st June 2018) - Li, Wen-Jing; Jiang, Luo-Luo; Gu, Changgui; Yang, Huijie
Abstract: Social influence widely exists in human society where people may be affected by others in the process of decision making due to their personal prestige or majority rule. It is interesting to quantize the impact of the influential individuals on the evolution of cooperation. Here, we proposed a model where two types of players are introduced in snowdrift game (SG): normal individuals and influential individuals. The former are payoff-driven in case of lacking social influence. Whereas under the condition of social influence, the former will copy the latter's strategies strictly. Yet, the latter act as coordinators, who may compromise to be in accordance with the majority in order to orchestrate collective actions. The results show that an effective mechanism may be evoked by an appropriate population density of influential individuals. By investigating dynamic patterns of optimum value, we discover that cooperators invade defector clusters from the boundaries, and dominate defectors eventually. Moreover, we also studied the cooperation frequency of both types of individuals evolving over time. It is observed that normal individuals have higher cooperation frequency initially. Later, influential individuals have higher cooperation level than normal ones, and keep it after the system stabilizes. In the process of solving coordination problems, influential individuals contribute to maintenance of rules and orders, which induce cooperation. These results may provide an insight into understanding the evolution of the individual behaviors and social orders in respect of social influence.